“Saintist Women”: The Empowerment of Students’ Ability in Manggarai Regency Through Toefl Test Training - Yulian Juita Ekalia; Ely Heldydiana Selamat; Ignasius Semana; Leonardus Par; Yakobus Sandiawan Asman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The aim of community service is to improve the community’s ability to master English by participating in TOEFL training in Manggarai Regency. This activity was carried out at UNIKA Santu Paulus Ruteng. The participants who attended were the people of the Manggarai district with the involvement of 30 participants. The techniques used in this activity are lectures, discussions, modeling, and exercises. This activity last for 1 week (7 days) consisting of pre-test, training/treatment, then post-test using Paired sample T-Test. Furthermore, this activity is carried out by distributing questionnaires to the public. The results obtained from this service activity are that this training activity is able to increase the participants’ TOEFL scores and increase their competence in listening, reading, and doing TOEFL grammar exercises. Likewise, the result of the questionnaire obtained was the same where 80% of the participants responded positively to this training activity. By joining this TOEFL training, participants find it helpful to master and comprehend how to do TOEFL questions easily.